U.S. Geological Survey Polar Bear Mark-Recapture Records, Alaska Portion of the Southern Beaufort Sea, 2001-2010 - US Geological Survey, Alaska Science Center; Bromaghin, Jeffrey F; Atwood, Todd C; Durner, George M (U.S. Geological Survey, 2015)
These data were collected by the U.S. Geological Survey, Alaska Science Center, Polar Bear Research Program as part of long-term on the southern Beaufort Sea polar bear population.